2021
DOI: 10.1016/j.tips.2020.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Metabolism as a Pharmacological Target

Abstract: L-Tryptophan is an essential amino acid required for protein synthesis. It undergoes an extensive and complex metabolism along several pathways, resulting in many bioactive molecules acting in various organs through different action mechanisms. Enzymes involved in its metabolism, metabolites themselves, or their receptors, represent potential therapeutic targets, which are the subject of dynamic research. Disruptions in L-tryptophan metabolism are reported in several neurological, metabolic, psychiatric, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
125
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(126 citation statements)
references
References 108 publications
(113 reference statements)
0
125
0
1
Order By: Relevance
“…Impaired production of AhR ligands has been observed in the intestinal microbiota of patients suffering from inflammatory bowel disease ( 45 ) and celiac disease ( 22 ). Given the critical impact of dietary AhR ligands on ILC3 numbers and the maintenance of barrier integrity, diet supplementation with AhR ligands, or AhR ligand-producing bacteria, is an attractive strategy to improve the treatment of inflammatory gastrointestinal diseases ( 24 ). However, a better understanding of the role of nutritional AhR ligands on the immune homeostasis of distant tissues and on myeloid cells will be essential to optimize these therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired production of AhR ligands has been observed in the intestinal microbiota of patients suffering from inflammatory bowel disease ( 45 ) and celiac disease ( 22 ). Given the critical impact of dietary AhR ligands on ILC3 numbers and the maintenance of barrier integrity, diet supplementation with AhR ligands, or AhR ligand-producing bacteria, is an attractive strategy to improve the treatment of inflammatory gastrointestinal diseases ( 24 ). However, a better understanding of the role of nutritional AhR ligands on the immune homeostasis of distant tissues and on myeloid cells will be essential to optimize these therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, after 4 weeks of tryptophan-low diet, the abundance of Lactobacillus reuteri is also decreased in the stomach ( 15 ). Of note, tryptophan is metabolized in the gut not only into AhR ligands by microbiota, but also through the serotonin and kynurenine pathways by host cells ( 5 , 24 ). Whether the observed alterations in microbiota composition are entirely dependent on changes in AhR ligands availability remains to be confirmed.…”
Section: Do Nutritional Ahr Ligands Influence Microbiota Composition?mentioning
confidence: 99%
“…In contrast, Cheng and colleagues recently set out to evaluate the existence of a causal relationship between metabolites of the tryptophan pathway and kidney function using a bidirectional Mendelian randomization analysis, and they revealed that the increased blood levels of tryptophan metabolites were a consequence rather than a cause of a reduced eGFR [ 24 ]. However, it is becoming clear that IDO has a complex role in chronic inflammatory and metabolic diseases and remains an interesting therapeutic target [ 25 ], however, in-depth knowledge about its regulation and interconnection to other enzyme systems is essential in the development of effective therapies [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is especially difficult to establish candidate probiotic strains as thriving members of complex the gut microbiome ecosystem, so the current paradigm of probiotic therapy could be transient at best. Currently, promising studies are exploring small molecules that act directly on host proteins such as IDO and AHR (69). A key hallmark of IBD is dysbiosis of the gut microbiome, or alteration of the abundance and distribution of gut bacteria (70,71).…”
Section: Microbial Uptake and Metabolism Of Trpmentioning
confidence: 99%